An Overview of the Work Ethic of a Timorese Traditional Ikat Weaver - Hermanus, Neltji Elisabeth F; Keraf, MKP Abdi; Wijaya, R. Pasifikus Ch. (Universitas Nusa Cendana, 2023)
Work ethic is a person's attitude, view, and belief toward his work. This study aims to describe the work ethic of traditional Timorese woven cloth weavers at Sentra Tenun Ina Ndao Kupang, which is seen based on work aspects such as moral obligations, work discipline, and pride in work results. This type of research is qualitative research. The primary informants in this study amounted to 6 people. The results of the study showed that the six informants saw work as a moral obligation in terms of being responsible for fulfilling their own needs as well as for others. In the aspect of work discipline, the six informants see work as a form of self-awareness of the rules that exist in the workplace and their sincerity in completing work. As well as in the aspect of pride in work results, the six informants see work as a form of appreciation for work results to improve the quality of their work. The implications of the results of this research for the weavers are that they become aware of what a work ethic is and the importance of having and improving a work ethic in individuals and groups when working to produce good work results.